Gibbsite solubility and aluminum speciation in alkaline nuclear waste containing nitrate, nitrite, and phosphate - Trent R. Graham; Ashley R. Kennedy; Winnie Liu; Daria V. Boglaienko; Robert G. Felsted; Jacob G. Morton; Micah P. Prange; Mark E. Bowden; Teresa L. Lemmon; Marie S. Swita; Hsiu-Wen Wang; Michael D. Britton; et al. (Chemical Engineering Journal, 2026)

A 2026 horizon scan for biodiversity conservation in South Africa - Colleen L. Seymour; Krystal A. Tolley; Tsungai Zengeya; Dian Spear; Jeran A. Cloete; Anisha Dayaram; Jessica M. da Silva; Graham J. Alexander; Kate Handley; Grant S. Joseph; Lavhelesani D. Simba; Kate Snaddon; et al. (Ambio, 2026)
Horizon scans identify potential changes, enabling proactive rather than reactive conservation strategies. Here, in a follow up to the 2020 horizon scan, 14 biodiversity professionals from different sectors identify ten emerging issues potentially relevant to biodiversity conservation in South Africa over the next 5–10 years. The issues identified highlight three critical needs: adaptive governance systems, cross-sectoral collaboration capacity, and vigilance around new technologies that may simultaneously offer solutions and create new environmental pressures. We plotted these issues along axes of social agreement and scientific certainty, to ascertain whether issues might be "simple" (amenable to solutions from science alone), "complicated" (socially agreed upon but technically complicated), "complex" (scientifically challenging and condisderable levels of social disagreement) or "chaotic" (high social disagreement and highly scientifically challenging). Only one issue was likely to be addressed with improved science alone, but the remainder were all “complex”, requiring social, economic and political engagement.

Resource availability and human activity shape the landscape distribution of white rhinoceros, a highly threatened African megaherbivore - Emilia S. M. Staegemann; Timothy Kuiper; Dave J. Druce; Graham I. H. Kerley; Siphesihle Mbongwa; Joris P. G. M. Cromsigt (Oecologia, 2026)
The megaherbivore concept suggests that mammals >1000 kg are insensitive to predation as adults. Consequently, their space use should be largely driven by resources. This does not account for the fact that megaherbivores have been hunted by humans for >100,000 years and likely evolved innate responses against human predation. Recent studies indeed show that megaherbivores, such as elephants and rhino, strongly respond to human voices. Few, however, have examined the relative influence of resource versus human risk drivers on the landscape use of megaherbivores. Using a long-term dataset from aerial rhino surveys and poaching events in Hluhluwe-iMfolozi Park, South Africa, we investigated how resource and human risk factors shape the landscape distribution of white rhinoceros ( Ceratotherium simum ). We used rainfall, fire, catena position, and terrain ruggedness as resource drivers and poaching intensity, and distance to human sound-generating infrastructure as human risk drivers. Both resource and human risk drivers affected rhino landscape distribution. Rhino preferred valley bottoms over midlands and uplands, and the use of the latter two habitats increased during the dry season. During drier wet seasons, rhinos increased their upland habitat use. Rhino avoided the park’s fenceline and other infrastructure (roads and camps). Poaching intensity did not influence rhino landscape use. Avoidance of human infrastructures may reduce the effective size of protected areas for rhino. Future work should assess how rhino respond to resources and risk over shorter timescales. Our findings encourage a re-evaluation of the megaherbivore concept to include humans as drivers of their ecology.

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Extent of the São Francisco Craton, South America: a mantle perspective - Nadine P. Cooper; James M. Scott; D. Graham Pearson; Rogerio G. Azzone; Felipe P. Leitzke; S. Woodland; Jose P. Donatti-Filho; M. Palmer; Malcolm R. Reid; Andrew J. Schaeffer (Mineralogy and Petrology, 2025)
Although cratons owe their longevity to thick, depleted and consequently buoyant sub-continental lithospheric mantle, their extents are commonly indicated by the known distribution of crustal rocks. However, the limits of a mapped cratonic area often do not match the seismically imaged thick sub-continental lithospheric mantle roots. New mantle xenolith petrology and geochemistry, combined with continental scale geophysical data, confirm the interpretation that the São Francisco Craton extends beyond the extent of surface exposures of Archean rocks. Mantle xenoliths from outside the typically recognised São Francisco Craton boundaries from the Limeira-1 and Redondão kimberlite diatremes have refractory olivine [Mg# ≤ 93, with Mg# = 100× molar Mg/(Mg + Fe); Limeira], high-Cr pyrope garnets (Cr 2 O 3 ≤ 7 wt% from Redondão), low bulk Al 2 O 3 < 1 wt%, and 187 Os/ 188 Os i = 0.11202–0.11916 (Limeira) and 0.10964–0.11576 (Redondão) that equate to Mesoproterozoic minimum T RD ages. Geothermobarometry indicates that the lithospheric thickness from which the Redondão xenolith suite was exhumed, extended to > 150 km at the time of eruption, similar to the lithosphere thickness estimated from garnet pyroxenites from the ‘on-craton’ Braúna field. The occurrence of thick, refractory and ancient lithosphere extending outside the known surface extent of the São Francisco Craton suggests that this cratonic nucleus is significantly larger than recognised at the surface. Based on the evidence reported in this study coupled with existing literature, we propose that the current limits of the São Francisco Craton nucleus should be revised to consider deep lithosphere to the north and southwest edges, despite these areas having younger rocks at the surface.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

DNA barcode assessment of Xanthium section Xanthium cockle burrs in Australia - David Gopurenko; Xiaocheng Zhu; R. M. S. P. Rathnayake; Hanwen Wu; Bruce A. Auld; James Hereward; Heather Smith; Stephen B. Johnson; Karen A. Kirkby; Graham W. Charles (Plant Systematics and Evolution, 2025)
Xanthium cockle burrs are invasive weeds in many countries, affecting local ecosystems and agriculture. All Xanthium in Australia are naturalised weeds from multiple overseas sources, but their taxonomic identities are contentious. In particular, species identities of four burr varieties or “complexes” under Xanthium section Xanthium in Australia are unclear. These complexes, commonly referred to as “Noogoora”, “Californian”, “Hunter”, and “South American” burr, are regarded as either varieties of a single species ( Xanthium strumarium ) or four separate species in the section. To genetically determine the species identities of these complexes in Australia, we compared their chloroplast DNA barcodes to reference sequences of vouchered Xanthium species reported by Tomasello (2018). We barcoded 173 plants from 26 sites consisting of single complex burrs and 175 plants from sites containing mixed burr complexes. Single complex sites contained either of two DNA barcode clades. One clade consisting of Noogoora and Californian burrs matched reference sequences of X. chinense . The second clade consisting of Hunter and South American burrs matched X. orientale . Genetic exchange between these two species in Australia was partially evident at some sites containing sympatric complexes or putative hybrids. Reference X. strumarium sequences were unmatched to the DNA barcodes of specimens sampled in Australia, and subsequently, we advise against future claims to a historical presence of this species in Australia. Our findings are significant for taxonomic treatment of Xanthium species in Australia and for consideration of source-specific biological controls of these weeds.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Hemisphere- and condition-specific alpha oscillations support semantic and spatial cognition in aging - Maggie P. Rempe; Danae S. Manta; Kayle Cohen; Ryan J. Glesinger; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Lucy K. Horne; Grant M. Garrison; Kennedy A. Kress; Lucas Weyrich; Chloe C. Casagrande; et al. (GeroScience, 2025)

Control of N-nitrosamine impurities in drug products: Progressing the current CPCA framework and supporting the derivation of robust compound specific acceptable intakes - David J. Ponting; Andreas Czich; Susan P. Felter; Susanne Glowienke; James S. Harvey; Raphael Nudelman; Joerg Schlingemann; Stephanie Simon; Graham F. Smith; Andrew Teasdale; Robert Thomas (Regulatory Toxicology and Pharmacology, 2025)

Corrigendum to “Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity” [Carbohydr. Polym. 347 (1 January 2025) 122686] - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

Dissecting the Enterococcal Polysaccharide Antigen (EPA) structure to explore innate immune evasion and phage specificity - Jessica L. Davis; Joshua S. Norwood; Robert E. Smith; Finn O'Dea; Krishna Chellappa; Michelle L. Rowe; Mike P. Williamson; Graham P. Stafford; Evguenii Vinogradov; Emmanuel Maes; Yann Guérardel; Stéphane Mesnage (Carbohydrate Polymers, 2025)

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Seagrass wasting disease prevalence and lesion area increase with invertebrate grazing across the northeastern Pacific - Lillian R. Aoki; Carmen J. Ritter; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Olivia J. Graham; Carla P. Gomes; Collin Gross; Timothy L. Hawthorne; Eliza Heery; Margot Hessing‐Lewis; Kevin Hovel; et al. (Ecology, 2025)
Disease is a key driver of community and ecosystem structure, especially when it strikes foundation species. In the widespread marine foundation species eelgrass ( Zostera marina ), outbreaks of wasting disease have caused large‐scale meadow collapse in the past, and the causative pathogen, Labyrinthula zosterae , is commonly found in meadows globally. Research to date has mainly focused on abiotic environmental drivers of seagrass wasting disease, but there is strong evidence from other systems that biotic interactions such as herbivory can facilitate plant diseases. How biotic interactions influence seagrass wasting disease in the field is unknown but is potentially important for understanding dynamics of this globally valuable and declining habitat. Here, we investigated links between epifaunal grazers and seagrass wasting disease using a latitudinal field study across 32 eelgrass meadows distributed from southeastern Alaska to southern California. From 2019 to 2021, we conducted annual surveys to assess eelgrass shoot density, morphology, epifauna community, and the prevalence and lesion area of wasting disease infections. We integrated field data with satellite measurements of sea surface temperature and used structural equation modeling to test the magnitude and direction of possible drivers of wasting disease. Our results show that grazing by small invertebrates was associated with a 29% increase in prevalence of wasting disease infections and that both the prevalence and lesion area of disease increased with total epifauna abundances. Furthermore, these relationships differed among taxa; disease levels increased with snail ( Lacuna spp.) and idoteid isopod abundances but were not related to abundance of ampithoid amphipods. This field study across 23° of latitude suggests a prominent role for invertebrate consumers in facilitating disease outbreaks with potentially large impacts on coastal seagrass ecosystems.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Stable carbon isotopes and bulk-sediment geochemistry as indicators of relative sea-level change in tidal marshes, mangroves and isolation basins: Application and developments - Graham P. Wilson; Jeremy M. Lloyd; Nicole S. Khan; Andrew C. Kemp (Quaternary Science Reviews, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Detection of mpox virus in wastewater provides forewarning of clinical cases in Canadian cities - Edgard M. Mejia; Nikho A. Hizon; Codey E. Dueck; Ravinder Lidder; Jade Daigle; Quinn Wonitowy; Nestor G. Medina; Umar P. Mohammed; Graham W. Cox; David Safronetz; Mable Hagan; Jim Strong; et al. (Science of The Total Environment, 2024)

Performance of Orbicella faveolata larval cohorts does not align with previously observed thermal tolerance of adult source populations - Yingqi Zhang; Shelby E. Gantt; Elise F. Keister; Holland Elder; Graham Kolodziej; Catalina Aguilar; Michael S. Studivan; Dana E. Williams; Dustin W. Kemp; Derek P. Manzello; Ian C. Enochs; Carly D. Kenkel (Global Change Biology, 2023)
Orbicella faveolata , commonly known as the mountainous star coral, is a dominant reef‐building species in the Caribbean, but populations have suffered sharp declines since the 1980s due to repeated bleaching and disease‐driven mortality. Prior research has shown that inshore adult O. faveolata populations in the Florida Keys are able to maintain high coral cover and recover from bleaching faster than their offshore counterparts. However, whether this origin‐specific variation in thermal resistance is heritable remains unclear. To address this knowledge gap, we produced purebred and hybrid larval crosses from O. faveolata gametes collected at two distinct reefs in the Upper Florida Keys, a nearshore site (Cheeca Rocks, CR) and an offshore site (Horseshoe Reef, HR), in two different years (2019, 2021). We then subjected these aposymbiotic larvae to severe (36°C) and moderate (32°C) heat challenges to quantify their thermal tolerance. Contrary to our expectation based on patterns of adult thermal tolerance, HR purebred larvae survived better and exhibited gene expression profiles that were less driven by stress response under elevated temperature compared to purebred CR and hybrid larvae. One potential explanation could be the compromised reproductive output of CR adult colonies due to repeated summer bleaching events in 2018 and 2019, as gametes originating from CR in 2019 contained less storage lipids than those from HR. These findings provide an important counter‐example to the current selective breeding paradigm, that more tolerant parents will yield more tolerant offspring, and highlight the importance of adopting a holistic approach when evaluating larval quality for conservation and restoration purposes.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Automated multi-beat tissue Doppler echocardiography analysis using deep neural networks - Elisabeth S. Lane; Jevgeni Jevsikov; Matthew J. Shun-shin; Niti Dhutia; Nasser Matoorian; Graham D. Cole; Darrel P. Francis; Massoud Zolgharni (Medical & Biological Engineering & Computing, 2023)

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

The Interplay Between Dimethyl Sulfide (DMS) and Methane (CH4) in a Coral Reef Ecosystem - Elisabeth S. M. Deschaseaux; Hilton B. Swan; Damien T. Maher; Graham B. Jones; Kai G. Schulz; Edwin P. Koveke; Kei Toda; Bradley D. Eyre (Frontiers in Marine Science, 2022)
Earth’s Radiation Budget is partly dictated by the fragile and complex balance between biogenic volatile organic compounds (BVOCs) and greenhouse gases (GHGs), which have the potential to impose cooling or warming once emitted to the atmosphere. Whilst methane (CH 4 ) is strictly associated with global warming due to its solar-radiation absorbing properties, dimethyl sulfide (DMS) is generally considered a cooling gas through the light scattering properties of its atmospheric oxidation products. However, DMS may also partially contribute to the Earth’s warming through a small portion of it being degraded to CH 4 in the water column. Coral reefs emit both DMS and CH 4 but they have not previously been simultaneously measured. Here, we report DMS and CH 4 fluxes as well as aerosol particle counts at Heron Island, southern Great Barrier Reef, during the austral summer of 2016. Sea-to-air DMS and CH 4 fluxes were on average 24.9 ± 1.81 and 1.36 ± 0.11 µmol m -2 d -1 , whilst intermediate (< 0.5-2.5 um) and large (> 2.5 um) particle number concentrations averaged 5.51 x 10 6 ± 1.73 x 10 5 m -3 and 1.15 x 10 6 ± 4.63 x 10 4 m -3 , respectively. Positive correlations were found between DMS emissions and the abundance of intermediate (R 2 = 0.1669, p < 0.001, n = 93) and large (R 2 = 0.0869, p = 0.004, n = 93) aerosol particles, suggesting that DMS sea-to-air emissions significantly contribute to the growth of existing particles to the measured size ranges at the Heron Island lagoon. Additionally, a strong positive correlation was found between DMS and CH 4 fluxes (R 2 = 0.7526, p < 0.00001, n = 93), suggesting that the emission of these volatile compounds from coral reefs is closely linked. The slope of the regression between DMS and CH 4 suggests that CH 4 emissions at the Heron Island lagoon represent 5% of that of DMS, which is consistent with the average sea-to-air fluxes reported in this study (i.e. 24.9 ± 1.81 µmol m -2 d -1 for DMS and 1.36 ± 0.11 for CH 4 ). These findings provide new insights on the complexity of BVOC and GHG emissions in coral reef systems and their potential role in climate regulation.

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients - Ayush Batra; Jeffrey R. Clark; Anthony K. Kang; Sareen Ali; Tulsi R. Patel; Nathan A. Shlobin; Steven C. Hoffman; Patrick H. Lim; Zachary S. Orban; Lavanya Visvabharathy; Edith L. Graham; David P. Sullivan; et al. (GeroScience, 2022)

Basaltic dykes and their xenoliths from the Gerroa–Kiama region, southern Sydney Basin, New South Wales: evidence for multiple intrusive episodes - S. Abu-Shamma; I. T. Graham; P. Lennox; G. Bann; A. Greig (Australian Journal of Earth Sciences, 2022)

Fields with no recent legume cultivation have sufficient nitrogen-fixing rhizobia for crops of faba bean (Vicia faba L.) - Marta Maluk; Francesc Ferrando-Molina; Laura Lopez del Egido; Adrian Langarica-Fuentes; Genet Gebre Yohannes; Mark W. Young; Peter Martin; Richard Gantlett; Greg Kenicer; Cathy Hawes; Graham S. Begg; Richard S. Quilliam; et al. (Plant and Soil, 2022)
Purpose (1) To assess the biological N fixation (BNF) potential of varieties of faba bean ( Vicia faba L.) cropped with or without compost in an experimental field-scale rotation with no recent history of legumes, (2) to enumerate soil populations of Rhizobium leguminosarum sv. viciae ( Rlv ), and to genetically characterize the nodulating Rlv strains, (3) compare BNF with other sites in Britain. Methods BNF was evaluated from 2012 to 2015 using 15 N natural abundance. Treatments were either PK fertilizer or compost. Soil rhizobial populations were determined using qPCR, the symbiotic rhizobia genotyped (16 S rRNA, nodA and nodD genes), and their BNF capacity assessed ex situ . The reliance of legumes on BNF at other British sites was estimated in a single season, and their nodulating symbionts examined. Results Faba bean obtained most of its N through BNF (>80%) regardless of variety or year. N-accumulation by cvs Babylon and Boxer increased with compost treatment in 2014/2015. Rhizobial populations were c. 10 5 -10 6 Rlv cells g −1 soil regardless of field or treatment. 157 Rlv microsymbionts grouped into two large nodAD clades; one mainly from V. faba , and the other from various legumes. All isolates nodulated, and some performed better than commercial inoculant strains. Conclusions Faba bean can provide most of its nitrogen through BNF and leave economically valuable residual N for subsequent crops. Recent legume cropping in northern Europe is not essential for effective nodulation: rhizobia may persist in a range of farmland locations. Nevertheless, there is the potential to apply elite rhizobial strains as inoculants in some soils.

Intradialytic cycling does not exacerbate microparticles or circulating markers of systemic inflammation in haemodialysis patients - Patrick J. Highton; Daniel S. March; Darren R. Churchward; Charlotte E. Grantham; Hannah M. L. Young; Matthew P. M. Graham-Brown; Seila Estruel; Naomi Martin; Nigel J. Brunskill; Alice C. Smith; James O. Burton; Nicolette C. Bishop (European Journal of Applied Physiology, 2022)
Purpose Patients receiving haemodialysis (HD) display elevated circulating microparticle (MP) concentration, tissue factor (TF) expression and markers of systemic inflammation, though regular intradialytic cycling (IDC) may have a therapeutic effect. This study investigated the impact of regular, moderate-intensity IDC on circulating MPs and inflammatory markers in unit-based HD patients. Methods Patients were cluster-randomised to intervention ( n = 20, age: 51.4 ± 18.1 years, body mass: 77.6 ± 18.3 kg, mean ± SD) or no-exercise control ( n = 20, 56.8 ± 14.0 years, 80.5 ± 26.5 kg). Intervention participants completed 30 min of moderate intensity (rating of perceived exertion [RPE] of 12–14) IDC, thrice weekly for 6 months. Pre-dialysis venous blood samples were obtained at 0, 3 and 6 months. Circulating MP phenotypes, cytokines, chemokine and MP TF expression were quantified using flow cytometry and cytometric bead array assays. Results Despite high exercise compliance (82%), no IDC-dependent effects were observed for any MP, cytokine or chemokine measure ( p ≥ 0.051, η ρ 2 ≤ 0.399) other than TNF-α ( p = 0.001, η ρ 2 = 0.186), though no significance was revealed upon post hoc analysis. Conclusion Six months of regular, moderate-intensity IDC had no effect on MPs, cytokines or chemokines. This suggests that the exercise did not exacerbate thrombotic or inflammatory status, though further functional assays are required to confirm this. Trial registration ISRCTN1129707, prospectively registered on 05/03/2015.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Spatial variation in direct and indirect effects of climate and productivity on species richness of terrestrial tetrapods - Elisa Barreto; Thiago F. Rangel; Marco Túlio P. Coelho; Fernanda A. S. Cassemiro; Niklaus E. Zimmermann; Catherine H. Graham (Global Ecology and Biogeography, 2021)
Aim We aimed to dissect the spatial variation of the direct and indirect effects of climate and productivity on global species richness of terrestrial tetrapods. Location Global. Time period Present. Major taxa studied Terrestrial tetrapods. Methods We used a geographically weighted path analysis to estimate and map the direct and indirect effects of temperature, precipitation and primary productivity on species richness of terrestrial tetrapods across the globe. Results We found that all relationships shift in magnitude, and even in direction, among taxonomic groups, geographical regions and connecting paths. Direct effects of temperature and precipitation are generally stronger than both indirect effects mediated by productivity and direct effects of productivity. Main conclusions Richness gradients seem to be driven primarily by effects of climate on organismal physiological limits and metabolic rates rather than by the amount of productive energy. Reptiles have the most distinct relationships across tetrapods, with a clear latitudinal pattern in the importance of temperature versus water.

Impacts of Stony Coral Tissue Loss Disease (SCTLD) on Coral Community Structure at an Inshore Patch Reef of the Upper Florida Keys Using Photomosaics - Graham Kolodziej; Michael S. Studivan; Arthur C. R. Gleason; Chris Langdon; Ian C. Enochs; Derek P. Manzello (Frontiers in Marine Science, 2021)
Since the appearance of stony coral tissue loss disease (SCTLD) on reefs off Miami in 2014, this unprecedented outbreak has spread across the entirety of Florida’s coral reef tract, as well as to many territories throughout the Caribbean. The endemic zone reached the upper Florida Keys by 2016, resulting in partial or complete mortality of coral colonies across numerous species. Disease was first observed at Cheeca Rocks (Islamorada, Florida) in the beginning of 2018, with reports of coral mortality peaking mid-year. The disease was still present at Cheeca Rocks as of March 2020, however, to a lesser degree compared to the initial outbreak. Annual monitoring efforts have been ongoing at Cheeca Rocks since 2012, including repeated benthic photomosaics of a 330 m 2 survey zone, spanning six replicate sites. As such, a repository of coral community composition data exists for before and after the disease outbreak that was analyzed to assess the impacts of SCTLD on reef communities at an upper Florida Keys inshore reef. Cheeca Rocks is hypothesized to be a resilient reef due to its persistent high coral cover despite its inshore location, which subjects corals to fluctuating water quality and marginal environmental conditions. Coral populations here have been shown to recover from bleaching events and heat stress with minimal coral mortality. Though colonies of coral species characterized as highly and moderately susceptible to SCTLD (e.g., Colpophyllia natans , Diploria labyrinthiformis , Pseudodiploria strigosa , Orbicella annularis , and O. faveolata ) suffered mortality as a result of the outbreak with an average loss of 16.42% relative cover by species, the overall impacts on coral cover and community structure were relatively low, contributing to a loss of total coral cover of only 1.65%. Comparison of photomosaic data to other studies indicate Cheeca Rocks may not have been affected as severely as other sites on Florida’s coral reef tract, underlying this site’s potential role in coral resilience to stressors including bleaching events, land-based pollution, and disease epizootics.

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

The extent and variability of storm‐induced temperature changes in lakes measured with long‐term and high‐frequency data - Jonathan P. Doubek; Orlane Anneville; Gaël Dur; Aleksandra M. Lewandowska; Vijay P. Patil; James A. Rusak; Nico Salmaso; Christian Torsten Seltmann; Dietmar Straile; Pablo Urrutia‐Cordero; Patrick Venail; Rita Adrian; et al. (Limnology and Oceanography, 2021)
The intensity and frequency of storms are projected to increase in many regions of the world because of climate change. Storms can alter environmental conditions in many ecosystems. In lakes and reservoirs, storms can reduce epilimnetic temperatures from wind‐induced mixing with colder hypolimnetic waters, direct precipitation to the lake's surface, and watershed runoff. We analyzed 18 long‐term and high‐frequency lake datasets from 11 countries to assess the magnitude of wind‐ vs. rainstorm‐induced changes in epilimnetic temperature. We found small day‐to‐day epilimnetic temperature decreases in response to strong wind and heavy rain during stratified conditions. Day‐to‐day epilimnetic temperature decreased, on average, by 0.28°C during the strongest windstorms (storm mean daily wind speed among lakes: 6.7 ± 2.7 m s −1 , 1 SD) and by 0.15°C after the heaviest rainstorms (storm mean daily rainfall: 21.3 ± 9.0 mm). The largest decreases in epilimnetic temperature were observed ≥2 d after sustained strong wind or heavy rain (top 5 th percentile of wind and rain events for each lake) in shallow and medium‐depth lakes. The smallest decreases occurred in deep lakes. Epilimnetic temperature change from windstorms, but not rainstorms, was negatively correlated with maximum lake depth. However, even the largest storm‐induced mean epilimnetic temperature decreases were typically

Creating leadership collectives for sustainability transformations - O. Care; M. J. Bernstein; M. Chapman; I. Diaz Reviriego; G. Dressler; M. R. Felipe-Lucia; C. Friis; S. Graham; H. Hänke; L. J. Haider; M. Hernández-Morcillo; H. Hoffmann; et al. (Sustainability Science, 2021)
Enduring sustainability challenges requires a new model of collective leadership that embraces critical reflection, inclusivity and care. Leadership collectives can support a move in academia from metrics to merits, from a focus on career to care, and enact a shift from disciplinary to inter- and trans-disciplinary research. Academic organisations need to reorient their training programs, work ethics and reward systems to encourage collective excellence and to allow space for future leaders to develop and enact a radically re-imagined vision of how to lead as a collective with care for people and the planet.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Geomechanical characterisation of organic-rich calcareous shale using AFM and nanoindentation - S. P. Graham; M. Rouainia; A. C. Aplin; P. Cubillas; T. D. Fender; P. J. Armitage (Rock Mechanics and Rock Engineering, 2021)
The geomechanical integrity of shale overburden is a highly significant geological risk factor for a range of engineering and energy-related applications including CO $$_2$$ 2 storage and unconventional hydrocarbon production. This paper aims to provide a comprehensive set of high-quality nano- and micro-mechanical data on shale samples to better constrain the macroscopic mechanical properties that result from the microstructural constituents of shale. We present the first study of the mechanical responses of a calcareous shale over length scales of 10 nm to 100 $$\upmu$$ μ m, combining approaches involving atomic force microscopy (AFM), and both low-load and high-load nanoindentation. PeakForce quantitative nanomechanical mapping AFM (PF-QNM) and quantitative imaging (QI-AFM) give similar results for Young’s modulus up to 25 GPa, with both techniques generating values for organic matter of 5–10 GPa. Of the two AFM techniques, only PF-QNM generates robust results at higher moduli, giving similar results to low-load nanoindentation up to 60 GPa. Measured moduli for clay, calcite, and quartz-feldspar are $$22 ± 2\,\hbox { GPa}$$ 22 ± 2 GPa , $$42 ± 8\,\hbox { GPa}$$ 42 ± 8 GPa , and $$55 ± 10\,\hbox { GPa}$$ 55 ± 10 GPa respectively. For calcite and quartz-feldspar, these values are significantly lower than measurements made on highly crystalline phases. High-load nanoindentation generates an unimodal mechanical response in the range of 40–50 GPa for both samples studied here, consistent with calcite being the dominant mineral phase. Voigt and Reuss bounds calculated from low-load nanoindentation results for individual phases generate the expected composite value measured by high-load nanoindentation at length scales of 100–600 $$\upmu$$ μ m. In contrast, moduli measured on more highly crystalline mineral phases using data from literature do not match the composite value. More emphasis should, therefore, be placed on the use of nano- and micro-scale data as the inputs to effective medium models and homogenisation schemes to predict the bulk shale mechanical response.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Mitochondrial ROS and Aging: Understanding Exercise as a Preventive Tool - Henver S. Brunetta; Andrew M. Holwerda; Luc J. C. van Loon; Graham P. Holloway (Journal of Science in Sport and Exercise, 2020)

Governing evolution: A socioecological comparison of resistance management for insecticidal transgenic Bt crops among four countries - Yves Carrière; Zachary S. Brown; Sharon J. Downes; Govind Gujar; Graham Epstein; Celso Omoto; Nicholas P. Storer; David Mota-Sanchez; Peter Søgaard Jørgensen; Scott P. Carroll (Ambio, 2020)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Resurrection of the sixgill shark Hexanchus vitulus Springer & Waller, 1969 (Hexanchiformes, Hexanchidae), with comments on its distribution in the northwest Atlantic Ocean - Toby S. Daly-Engel; Ivy E. Baremore; R. Dean Grubbs; Simon J. B. Gulak; Rachel T. Graham; Michael P. Enzenauer (Marine Biodiversity, 2019)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

Cuspidaria cochinensis Preston, 1916 transferred to the Corbulidae (Mollusca, Bivalvia) and assigned to the genus Cuneocorbula - P. Graham Oliver; P. R. Jayachandran; S. Bijoy Nandan (Marine Biodiversity, 2018)

Steroid hormones in environmental matrices: extraction method comparison - Gangadhar Andaluri; Rominder P. S. Suri; Kendon Graham (Environmental Monitoring and Assessment, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Field Measurement of Fluorescent Dissolved Organic Material as a Means of Early Detection of Leachate Plumes - P. W. Graham; A. Baker; M. S. Andersen; I. Acworth (Water, Air, & Soil Pollution, 2015)

Ancient Gondwana break‐up explains the distribution of the mycoheterotrophic family Corsiaceae (Liliales) - Constantijn B. Mennes; Vivienne K. Y. Lam; Paula J. Rudall; Stephanie P. Lyon; Sean W. Graham; Erik F. Smets; Vincent S. F. T. Merckx (Journal of Biogeography, 2015)
Aim Many plant families have a disjunct distribution across the southern Pacific Ocean, including the mycoheterotrophic family Corsiaceae, which provides a prime example of this biogeographical pattern. A better grasp of the family's evolutionary relationships is needed to understand its historical biogeography. We therefore aimed to (1) test the uncertain monophyly of Corsiaceae, (2) define its phylogenetic position, and (3) estimate divergence times for the family, allowing us to assess whether the distribution of the family is the result of vicariance. Location Southern South America and Australasia. Methods We analysed various combinations of mitochondrial and nuclear data to address the monophyly, phylogenetic position and age of Corsiaceae. To test its monophyly, we used a three‐locus data set including most monocot orders, and to infer its exact phylogenetic position, we used a five‐locus extended data set. We corroborated these findings using an independent plastome dataset. We then used a two‐locus dataset with taxa from all monocot orders, and a three‐locus dataset containing only taxa of Liliales, to estimate divergence times using a fossil‐calibrated uncorrelated lognormal relaxed‐clock approach. Results Corsiaceae is a monophyletic family and the sister group of Campynemataceae. This clade is the sister group of all other Liliales. The crown age of Corsiaceae is estimated to be 53 Ma (95% confidence interval 30–76 Ma). Main conclusions Corsiaceae is an ancient family of mycoheterotrophic plants, whose crown age overlaps with the plate‐tectonic split of Gondwana, consistent with a vicariance‐based explanation for its current distribution.

Minimizing the biodiversity impact of Neotropical oil palm development - James J. Gilroy; Graham W. Prescott; Johann S. Cardenas; Pamela González del Pliego Castañeda; Andrés Sánchez; Luis E. Rojas‐Murcia; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2015)
Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland–forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region – improved cattle pasture – together with those of surrounding natural forests. We show that oil palm plantations have similar or higher species richness across all four taxonomic groups than improved pasture. For dung beetles, species richness in oil palm was equal to that of forest, whereas the other three taxa had highest species richness in forests. Hierarchical modelling of species occupancy probabilities indicated that oil palm plantations supported a higher proportion of species characteristic of forests than did cattle pastures. Across the bird community, occupancy probabilities within oil palm were positively influenced by increasing forest cover in a surrounding 250 m radius, whereas surrounding forest cover did not strongly influence the occurrence of other taxonomic groups in oil palm. Overall, our results suggest that the conversion of existing improved pastures to oil palm has limited negative impacts on biodiversity. As such, existing cattle pastures of the Colombian Llanos could offer a key opportunity to meet governmental targets for oil palm development without incurring significant biodiversity costs. Our results also highlight the value of preserving remnant forests within these agricultural landscapes, protecting high biodiversity and exporting avian ‘spill‐over’ effects into oil palm plantations.

To what extent do long-duration high-volume dam releases influence river–aquifer interactions? A case study in New South Wales, Australia - P. W. Graham; M. S. Andersen; M. F. McCabe; H. Ajami; A. Baker; I. Acworth (Hydrogeology Journal, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Groundwater residence time in a dissected and weathered sandstone plateau: Kulnura–Mangrove Mountain aquifer, NSW, Australia - D. I. Cendón; S. I. Hankin; J. P. Williams; M. Van der Ley; M. Peterson; C. E. Hughes; K. Meredith; I. T. Graham; S. E. Hollins; V. Levchenko; R. Chisari (Australian Journal of Earth Sciences, 2014)

Implications of Macroalgal Isolation by Distance for Networks of Marine Protected Areas - HALLEY M. S. DURRANT; CHRISTOPHER P. BURRIDGE; BRENDAN P. KELAHER; NEVILLE S. BARRETT; GRAHAM J. EDGAR; MELINDA A. COLEMAN (Conservation Biology, 2014)
The global extent of macroalgal forests is declining, greatly affecting marine biodiversity at broad scales through the effects macroalgae have on ecosystem processes, habitat provision, and food web support. Networks of marine protected areas comprise one potential tool that may safeguard gene flow among macroalgal populations in the face of increasing population fragmentation caused by pollution, habitat modification, climate change, algal harvesting, trophic cascades, and other anthropogenic stressors. Optimal design of protected area networks requires knowledge of effective dispersal distances for a range of macroalgae. We conducted a global meta‐analysis based on data in the published literature to determine the generality of relation between genetic differentiation and geographic distance among macroalgal populations. We also examined whether spatial genetic variation differed significantly with respect to higher taxon, life history, and habitat characteristics. We found clear evidence of population isolation by distance across a multitude of macroalgal species. Genetic and geographic distance were positively correlated across 49 studies; a modal distance of 50–100 km maintained F ST Implicaciones del Aislamiento por Distancia de Macroalgas para Redes de Áreas Marinas Protegidas

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

Bovine IFNGR2, IL12RB1, IL12RB2, and IL23R polymorphisms and MAP infection status - Sameer D. Pant; Chris P. Verschoor; Alicia M. Skelding; Flavio S. Schenkel; Qiumei You; Graham A. Biggar; David F. Kelton; Niel A. Karrow (Mammalian Genome, 2011)

Fresh Water Inflow and Oyster Productivity in Apalachicola Bay, FL (USA) - Autumn J. Oczkowski; F. Graham Lewis; Scott W. Nixon; H. Lee Edmiston; Rebecca S. Robinson; Jeffrey P. Chanton (Estuaries and Coasts, 2011)

Submarine hydrothermal activity and gold-rich mineralization at Brothers Volcano, Kermadec Arc, New Zealand - Cornel E. J. de Ronde; Gary J. Massoth; David A. Butterfield; Bruce W. Christenson; Junichiro Ishibashi; Robert G. Ditchburn; Mark D. Hannington; Robert L. Brathwaite; John E. Lupton; Vadim S. Kamenetsky; Ian J. Graham; Georg F. Zellmer; et al. (Mineralium Deposita, 2011)

How Clustering Dynamics Influence Lumber Utilization Patterns in the Amish-Based Furniture Industry in Ohio - Matthew S. Bumgardner; Gary W. Graham; P. Charles Goebel; Robert L. Romig (Journal of Forestry, 2011)
Preliminary studies have suggested that the Amish-based furniture and related products manufacturing cluster located in and around Holmes County, Ohio, uses sizeable quantities of hardwood lumber. The number of firms within the cluster has grown even as the broader domestic furniture manufacturing sector has contracted. The present study was undertaken in 2008 (spring/summer) to develop lumber use estimates specific to Amish manufacturing and provide more detail regarding the impacts of clustering on lumber consumption patterns. Results, based on 196 firms responding to a survey, suggested that lumber use ratios (bd ft per employee) differed among firms of different sizes and type of product manufactured, but in aggregate was similar to the broader US furniture industry. Red oak was the most commonly used species. Local suppliers of hardwood lumber and components were used extensively by most firms. The study confirmed that the Holmes County furniture cluster was important to regional hardwood demand, facilitated by well-developed supply chains that enable high specialization and enhance aggregate productivity among the numerous small manufacturers.

Lack of evidence for vertical transmission of SAV 3 using gametes of Atlantic salmon, Salmo salar L., exposed by natural and experimental routes - R T Kongtorp; A Stene; P A Andreassen; V Aspehaug; D A Graham; T M Lyngstad; A B Olsen; R S Olsen; M Sandberg; N Santi; C Wallace; O Breck (Journal of Fish Diseases, 2010)
Pancreas disease (PD) is an important cause of losses in farmed salmonids in Norway, the United Kingdom and Ireland. As the spread of salmonid alphavirus (SAV), the causal agent, to naïve populations is of major concern to the farming industry, it is important to uncover the transmission routes of the virus. This study was conducted to investigate the potential for vertical transmission of SAV subtype 3. Progeny of broodstock with signs of late‐stage PD and persistent RT‐PCR signals for SAV were followed from fertilization to smoltification in an experimental facility. Fertilized ova were either not disinfected or taken through one of three different disinfection regimes. Also, ova and milt from uninfected broodfish from a different population were exposed to a cell‐cultured strain of SAV 3 immediately before fertilization to simulate a viraemic phase in parent fish. A group of uninfected controls were also included in the study. Fertilized ova from bath exposed and negative control groups were double disinfected. Following fertilization, experimental fish went through a normal freshwater phase. However, fry were stressed at first feeding to enhance replication of possibly latent virus. Smoltification was induced by an artificial light regime, and experimental fish were followed to the late smoltification phase. Selected samples were investigated by real‐time RT‐PCR for SAV, by histology for evidence of PD and by serology for neutralising antibodies against SAV. All analysed samples of progeny were negative. This result shows that SAV 3 is not readily transmitted vertically from parents to offspring. Additional negative PCR results from salmon sampled in commercial hatcheries support these findings. Also, recent studies have shown that risk factors for the horizontal transmission route explain the vast majority of PD outbreaks in Norway. It is concluded that if it happens at all, vertical transmission is of minor importance in the spread of SAV 3.

El Niño, grazers and fisheries interact to greatly elevate extinction risk for Galapagos marine species - GRAHAM J. EDGAR; STUART A. BANKS; MARGARITA BRANDT; RODRIGO H. BUSTAMANTE; ANGEL CHIRIBOGA; SYLVIA A. EARLE; LAUREN E. GARSKE; PETER W. GLYNN; JACK S. GROVE; SCOTT HENDERSON; CLEVE P. HICKMAN; KATHY A. MILLER; et al. (Global Change Biology, 2010)
Comparisons between historical and recent ecological datasets indicate that shallow reef habitats across the central Galapagos Archipelago underwent major transformation at the time of the severe 1982/1983 El Niño warming event. Heavily grazed reefs with crustose coralline algae (‘urchin barrens’) replaced former macroalgal and coral habitats, resulting in large local and regional declines in biodiversity. Following recent threat assessment workshops, a total of five mammals, six birds, five reptiles, six fishes, one echinoderm, seven corals, six brown algae and nine red algae reported from coastal environments in Galapagos are now recognized as globally threatened. The 2008 International Union for the Conservation of Nature (IUCN) Red List includes 43 of these species, while two additional species (Galapagos damsel Azurina eupalama and 24‐rayed sunstar Heliaster solaris ) not seen for > 25 years also fulfil IUCN threatened species criteria. Two endemic species (Galapagos stringweed Bifurcaria galapagensis and the damselfish A. eupalama ) are now regarded as probably extinct, while an additional six macroalgal species ( Dictyota galapagensis, Spatoglossum schmittii, Desmarestia tropica, Phycodrina elegans, Gracilaria skottsbergii and Galaxaura barbata ) and the seastar H. solaris are possibly extinct. The removal of large lobster and fish predators by artisanal fishing probably magnified impacts of the 1982/1983 El Niño through a cascade of indirect effects involving population expansion of grazing sea urchins. Marine protected areas with adequate enforcement are predicted to ameliorate but not eliminate ecosystem impacts caused by increasing thermal anomalies associated with El Niño and global climate change.

Sub-lingual oral fistulas in Sooty Terns (Onychoprion fuscata) - S. James Reynolds; Graham R. Martin; Colin P. Wearn; B. John Hughes (Journal of Ornithology, 2009)

Three new Phaeoacremonium species on grapevines in New Zealand - A. B. Graham; P. R. Johnston; B. S. Weir (Australasian Plant Pathology, 2009)

Exploitation and habitat degradation as agents of change within coral reef fish communities - S. K. WILSON; R. FISHER; M. S. PRATCHETT; N. A. J. GRAHAM; N. K. DULVY; R. A. TURNER; A. CAKACAKA; N. V. C. POLUNIN; S. P. RUSHTON (Global Change Biology, 2008)
Over‐exploitation and habitat degradation are the two major drivers of global environmental change and are responsible for local extinctions and declining ecosystem services. Here we compare the top‐down effect of exploitation by fishing with the bottom‐up influence of habitat loss on fish communities in the most diverse of ecological systems, coral reefs. Using a combination of multivariate techniques and path analyses, we illustrate that the relative importance of coral cover and fishing in controlling fish abundance on remote Fijian reefs varies between species and functional groups. A decline in branching Acropora coral is strongly associated with a decline in abundance of coral‐feeding species, and a decrease in coral‐associated habitat complexity, which has indirectly contributed to reduced abundance of small‐bodied damselfish. In contrast, reduced fishing pressure, brought about by declining human populations and a shift to alternate livelihoods, is associated with increased abundance of some piscivores and fisheries target species. However, availability of prey is controlled by coral‐associated habitat complexity and appears to be a more important driver of total piscivore abundance compared with fishing pressure. Effects of both fishing and coral loss are stronger on individual species than functional groups, as variation in the relative importance of fishing or coral loss among species within the same functional group attenuated the impact of either of these potential drivers at the functional level. Overall, fishing continues to have an influence on Fijian fish communities; however, habitat loss is currently the overriding agent of change. The importance of coral loss mediated by climate change is expected to have an increasing contribution to fish community dynamics, particularly in remote locations or where the influence of fishing is waning.

Detection heterogeneity in underwater visual‐census data - M. A. MacNeil; N. A. J. Graham; M. J. Conroy; C. J. Fonnesbeck; N. V. C. Polunin; S. P. Rushton; P. Chabanet; T. R. McClanahan (Journal of Fish Biology, 2008)
This study shows how capture–mark–recapture (CMR) models can provide robust estimates of detection heterogeneity (sources of bias) in underwater visual‐census data. Detection biases among observers and fish family groups were consistent between fished and unfished reef sites in Kenya, even when the overall level of detection declined between locations. Species characteristics were the greatest source of detection heterogeneity and large, highly mobile species were found to have lower probabilities of detection than smaller, site‐attached species. Fish family and functional‐group detectability were also found to be lower at fished locations, probably due to differences in local abundance. Because robust CMR models deal explicitly with sampling where not all species are detected, their use is encouraged for studies addressing reef‐fish community dynamics.

Heterogeneity in the distribution of genetically modified and conventional oilseed rape within fields and seed lots - Graham S. Begg; Martin J. Elliott; Danny W. Cullen; Pietro P. M. Iannetta; Geoff R. Squire (Transgenic Research, 2008)

Characterisation and partial sequence analysis of two novel cypoviruses isolated from the winter moth Operophtera brumata (Lepidoptera: Geometridae) - Robert I. Graham; Shujing Rao; Steven M. Sait; Peter P. C. Mertens; Rosemary S. Hails; Robert D. Possee (Virus Genes, 2007)

Sources of uncertainty in the quantification of genetically modified oilseed rape contamination in seed lots - Graham S. Begg; Danny W. Cullen; Pietro P. M. Iannetta; Geoff R. Squire (Transgenic Research, 2007)

Genetic structure of introduced European fallow deer (Dama dama dama) in Tasmania, Australia - Lee S. Webley; Kyall R. Zenger; Graham P. Hall; Desmond W. Cooper (European Journal of Wildlife Research, 2007)

Multiple disturbances and the global degradation of coral reefs: are reef fishes at risk or resilient? - SHAUN K. WILSON; NICHOLAS A. J. GRAHAM; MORGAN S. PRATCHETT; GEOFFREY P. JONES; NICHOLAS V. C. POLUNIN (Global Change Biology, 2006)
Increased frequency of disturbances and anthropogenic activities are predicted to have a devastating impact on coral reefs that will ultimately change the composition of reef associated fish communities. We reviewed and analysed studies that document the effects of disturbance‐mediated coral loss on coral reef fishes. Meta‐analysis of 17 independent studies revealed that 62% of fish species declined in abundance within 3 years of disturbances that resulted in >10% decline in coral cover. Abundances of species reliant on live coral for food and shelter consistently declined during this time frame, while abundance of some species that feed on invertebrates, algae and/or detritus increased. The response of species, particularly those expected to benefit from the immediate loss of coral, is, however, variable and is attributed to erratic replenishment of stocks, ecological versatility of species and sublethal responses, such as changes in growth, body condition and feeding rates. The diversity of fish communities was found to be negatively and linearly correlated to disturbance‐mediated coral loss. Coral loss >20% typically resulted in a decline in species richness of fish communities, although diversity may initially increase following small declines in coral cover from high coverage. Disturbances that result in an immediate loss of habitat complexity (e.g. severe tropical storms), have a greater impact on fishes from all trophic levels, compared with disturbances that kill corals, but leave the reef framework intact (e.g. coral bleaching and outbreaks of Acanthaster planci ). This is most evident among small bodied species and suggests the long‐term consequences of coral loss through coral bleaching and crown‐of‐thorn starfish outbreaks may be much more substantial than the short‐term effects currently documented.

Clusterin/Apolipoprotein J up-regulation after zinc exposure, replicative senescence or differentiation of human haematopoietic cells - Ioannis P. Trougakos; Graham Pawelec; Christos Tzavelas; Triantaphillia Ntouroupi; Efstathios S. Gonos (Biogerontology, 2006)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Modelling the role of intracolonial genetic diversity on regulation of brood temperature in honey bee (Apis mellifera L.) colonies - S. Graham; M. R. Myerscough; J. C. Jones; B. P. Oldroyd (Insectes Sociaux, 2006)

Evaluating Ecological Condition Using Soil Biogeochemical Parameters and Near Infrared Reflectance Spectra - M. J. Cohen; S. Dabral; W. D. Graham; J. P. Prenger; W. F. Debusk (Environmental Monitoring and Assessment, 2006)

Maple Syrup Production in Ohio and the Impact of Ohio State University (OSU) Extension Programming - Gary W. Graham; P. Charles Goebel; Randall B. Heiligmann; Matthew S. Bumgardner (Journal of Forestry, 2006)
The maple syrup industry in Ohio, which ranks fifth in total production in the United States, is comprised primarily of small family owned operations that are served by The Ohio State University (OSU) Extension system. We evaluated the effectiveness of OSU Extension educational programming designed to improve sugarbush and sugarhouse management through a survey administered at the three 2004 Ohio Maple Days workshops. Most survey respondents indicated that after attending past maple syrup workshops they implemented changes that were relatively simple and inexpensive; however, most indicated they are interested in learning more about technologies that increase production and maple syrup quality.

Forest Roads as Partial Barriers to Terrestrial Salamander Movement - DAVID M. MARSH; GRAHAM S. MILAM; NICHOLAS P. GORHAM; NOELLE G. BECKMAN (Conservation Biology, 2005)
Roads can fragment animal populations by disrupting movement among formerly continuous habitats. Although models have demonstrated that disrupted movement can contribute to long‐term extinction, there are few empirical data on the effects of roads on animal movement. We used displacement and homing experiments to determine whether forest roads are barriers to the movement of terrestrial salamanders. We displaced 1471 red‐backed salamanders (Plethodon cinereus) across five forest roads and compared return rates to those of salamanders displaced equal distances toward the forest interior. Roads significantly reduced the return rate of salamanders, with a mean reduction of 51%. Steep roadside verges further reduced return rates, particularly for salamanders moving downhill across verges. The permeability of roads to salamander movement did not appear to be related to road surface type. Gravel roads had both the highest and lowest observed permeability with the two paved roads intermediate between these. We conclude that narrow forest roads are partial barriers to salamander movement and that steep roadside verges may exacerbate these effects.

An assessment of European pig diversity using molecular markers: Partitioning of diversity among breeds - Louis Ollivier; Lawrence Alderson; Gustavo C. Gandini; Jean-Louis Foulley; Chris S. Haley; Ruth Joosten; Annemieke P. Rattink; Barbara Harlizius; Martien A. M. Groenen; Yves Amigues; Marie-Yvonne Boscher; Geraldine Russell; et al. (Conservation Genetics, 2005)

Sugarcane biotechnology: The challenges and opportunities - Prakash Lakshmanan; R. Jason Geijskes; Karen S. Aitken; Christopher L. P. Grof; Graham D. Bonnett; Grant R. Smith (In Vitro Cellular & Developmental Biology - Plant, 2005)

The origin and spread of the HFE-C282Y haemochromatosis mutation - S. Distante; K.J.H. Robson; J. Graham-Campbell; A. Arnaiz-Villena; P. Brissot; Mark Worwood (Human Genetics, 2004)

Seismic Hazard and Risk Assessment for Tulbagh, South Africa: Part II – Assessment of Seismic Risk - A. Kijko; S. J. P. Retief; G. Graham (Natural Hazards, 2003)

Characterization and evaluation of North American Trifolium ambiguum -nodulating rhizobia - M.-S. Beauregard; P. Seguin; C. C. Sheaffer; P. H. Graham (Biology and Fertility of Soils, 2003)

Seismic Hazard and Risk Assessment for Tulbagh, South Africa: Part I – Assessment of Seismic Hazard - A. Kijko; S. J. P. Retief; G. Graham (Natural Hazards, 2002)

Water balance modelling in the Baltic Sea drainage basin - analysis of meteorological and hydrological approaches - L. P. Graham; S. Bergstrm (Meteorology and Atmospheric Physics, 2001)

A comprehensive model inter-comparison study investigating the water budget during the BALTEX-PIDCAP period - D. Jacob; B. J. J. M. Van den Hurk; U. Andr; G. Elgered; C. Fortelius; L. P. Graham; S. D. Jackson; U. Karstens; Chr. Kpken; R. Lindau; R. Podzun; B. Rockel; et al. (Meteorology and Atmospheric Physics, 2001)

Mean Annual Temperature and Total Annual Precipitation Trends at Canadian Biosphere Reserves - James P. Hamilton; Graham S. Whitelaw; Adam Fenech (Environmental Monitoring and Assessment, 2001)

RFLP mapping of manganese efficiency in barley - M. A. Pallotta; R. D. Graham; P. Langridge; D. H. B. Sparrow; S. J. Barker (Theoretical and Applied Genetics, 2000)

Unprecedented Low Levels of Genetic Variation and Inbreeding Depression in an Island Population of the Black‐Footed Rock‐Wallaby - Mark D. B. Eldridge; Juliet M. King; Anne K. Loupis; Peter B. S. Spencer; Andrea C. Taylor; Lisa C. Pope; Graham P. Hall (Conservation Biology, 1999)
It has been argued that demographic and environmental factors will cause small, isolated populations to become extinct before genetic factors have a significant negative impact. Islands provide an ideal opportunity to test this hypothesis because they often support small, isolated populations that are highly vulnerable to extinction. To assess the potential negative impact of isolation and small population size, we compared levels of genetic variation and fitness in island and mainland populations of the black‐footed rock‐wallaby ( Petrogale lateralis [Marsupialia: Macropodidae]). Our results indicate that the Barrow Island population of P. lateralis has unprecedented low levels of genetic variation ( H e = 0.053, from 10 microsatellite loci) and suffers from inbreeding depression (reduced female fecundity, skewed sex ratio, increased levels of fluctuating asymmetry). Despite a long period of isolation ( ∼ 1600 generations) and small effective population size ( N e ∼ 15), demographic and environmental factors have not yet driven this population to extinction. Nevertheless, it has been affected significantly by genetic factors. It has lost most of its genetic variation and become highly inbred ( F e = 0.91), and it exhibits reduced fitness. Because several other island populations of P. lateralis also exhibit exceptionally low levels of genetic variation, this phenomenon may be widespread. Inbreeding in these populations is at a level associated with high rates of extinction in populations of domestic and laboratory species. Genetic factors cannot then be excluded as contributing to the extinction proneness of small, isolated populations.

Noninvasive Delineation of Normal Right Ventricular Contractile Motion With Magnetic Resonance Imaging Myocardial Tagging - Stacy S. Klein; Thomas P. Graham, Jr.; Christine H. Lorenz (Annals of Biomedical Engineering, 1998)

Novel approach to investigate a source of microbial contamination of central venous catheters - T. S. J. Elliott; H. A. Moss; S. E. Tebbs; I. C. Wilson; R. S. Bonser; T. R. Graham; L. P. Burke; M. H. Faroqui (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Exchange of colicin receptor capacity between strains of Escherichia coli sensitive or resistant to colicin K-K235 - David P. Brunner; Gary S. Graham; Ronald W. Treick (Archives of Microbiology, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Report of committee on the genetics and cytology of tuber-bearingSolanums - R. W. Hougas; K. M. Graham; A. E. Kehr; P. Grun; S. J. Peloquin; F. I. Lauer; R. Plaisted; R. W. Buck; D. A. Young; F. L. Haynes; L. A. Dionne (American Journal of Potato Research, 1959)